2004
DOI: 10.1517/14656566.5.4.819
|View full text |Cite
|
Sign up to set email alerts
|

The management of leptospirosis

Abstract: How to quickly identify patients who should be treated for leptospirosis is a challenge. The interest of polymerase chain reaction (PCR) assays is currently being evaluated and rapid tests which can be used outside of the specialised laboratory, have recently been developed. Leptospires are sensitive to many antibiotics and few clinical studies have been made to compare different treatment options. Doxycycline is standard therapy in early leptospirosis treatment and chemoprophylaxis. Intravenous penicillin has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
0
21
0
3
Order By: Relevance
“…Oküler lezyonlarda Jarisch-Herxheimer reaksiyonu sifilis, Whipple hastal›¤›, leptospirozis ve Lyme hastal›¤› ile de rapor edilmifltir. [54][55][56][57] ATT ile paradoksik kötüleflme oküler TB'da ve özellik-le serpijinöz benzeri koroidit tablosunda bildirilmifltir. [49][50][51] 4.…”
Section: Subretinal Abseunclassified
“…Oküler lezyonlarda Jarisch-Herxheimer reaksiyonu sifilis, Whipple hastal›¤›, leptospirozis ve Lyme hastal›¤› ile de rapor edilmifltir. [54][55][56][57] ATT ile paradoksik kötüleflme oküler TB'da ve özellik-le serpijinöz benzeri koroidit tablosunda bildirilmifltir. [49][50][51] 4.…”
Section: Subretinal Abseunclassified
“…[1,2,3] Detection of DNA: DNA hybridization techniques or nucleic acid amplification procedures, including polymerase chain reaction (PCR), can be used to detect the presence of leptospira in body ß uids or culture supernatants. [2,3,5,50,51] …”
Section: Investigationsmentioning
confidence: 99%
“…[13] Treatment with penicillin or tetracycline (in children > 9 years of age) should be instituted as soon as the diagnosis is suspected. [1][2][3][4][5][6]36,42,51,56] It has been shown that treatment within one week of onset of fever can shorten the clinical course and decrease the severity of the infection. [1,2,57] Parenteral penicillin G (6-8 million U/m 2 /day given intravenously in divided doses every 4 hours for 7 days) is the drug of choice.…”
Section: Treatmentmentioning
confidence: 99%
“…The clinical presentations are diverse, ranging from undifferentiated fever to fulminant disease. Anicteric leptospirosis is the most common, occurring in 80% of cases (Faucher et al 2004). Meningitis can occur (Sperber & Schleupner 1989, Gollop et al 1990, Torre et al 1994, Romero et al 1998, Silva et al 2002, Karande et al 2005, de Souza et al 2006, Merwick et al 2008) and this form of leptospiral infection can be confused with other aseptic meningitis (Nelsen et al 1993, de Almeida et al 2007).…”
mentioning
confidence: 99%